Partisipasi Politik Online Generasi Z Pada Pemilihan Presiden Indonesia 2019 - Heni Putri Yolanda; Umar Halim (CoverAge: Journal of Strategic Communication, 2020)
The purpose of this study is to examine online political participation among Generation Z. Many previous studies have reviewed offline and onlie political participation. The offline participation is measured by conventional and non-conventional, while online participation has not been much studied in the form of dimensions. Then online participation in this study will be examined with the level of digital literacy from the concept of Digital Divide. The sample in this study amounted to 92 respondents from the students of the Faculty of Communication, University of Pancasila. Overall, results showed that online political participation in the form of instrumental and informative is mostly utilized by the majority of respondents. While the strategic participation were very few carried out by respondents (7.6% - 17.3%). The results of this study can also be concluded that participation in watching, reading and seeking political information is more done by generation Z compared to participation involving other people such as interacting and influencing people to choose certain candidates.